Relevance of Philippine policies for muslim-friendly ecotourism management in adapting the climate change challenges - Tagoranao, Mariam Saidano; Gamon, Alizaman Dumangcag (IOP Publishing, 2019)
The impact of climate change on the natural environment has been a common case affecting the ecotourism management in Mindanao. There are many challenges and threats facing the ecotourism development, in particular, mitigating natural hazard and preserving a Muslim-friendly environment. The government needs policies for sustainable development, by improving an efficient use of natural resources and infrastructures for less greenhouse gas emissions (GHG), and provide permissible services and livelihood for poverty reduction to help the realizations of Millennium Development Goals (MDGs). Developing the Muslim-friendly ecotourism destinations, particularly in the Bangsamoro Autonomous Muslim Regions (BARMM) can overshadow the environmental risk and it will provide economic development and health protection to the local people and the tourists. The findings will show that aside from the Tourism Act 2009 and the climate Change Act (Republic Act 9729), the presence of wellformulated policies and guidelines on ecotourism in adapting the climate change will widen the possibilities for the people to further benefit from ecotourism development. In conclusion, it is of great importance that in facing the climate changes, the government must have strict environmental standards compounded by strict enforcement. However, for paradigm shift, it is necessary to be reminded that “we have to accept the evils of global development along with its blessings”.